WAKTU PENYELESAIAN PROYEK KONSTRUKSI MENGGUNAKAN PRECEDENCE DIAGRAM METHOD DAN LINE OF BALANCE - ASTAWA, I WAYAN YOGA; TASTRAWATI, NI KETUT TARI; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 9 No 3 (2020)DO - 10.24843/MTK.2020.v09.i03.p298, 2020)
Project is any work that has a beginning and ending, consisting of several jobs/activities that must be carried out in a certain order. Contractors typically use the Gantt Chart Method in scheduling home construction projects so that it is difficult to know the impact caused by the late completion of work on scheduling the entire project. The purpose of this study is to determine the time needed to complete two housing units using the Precedence Diagram Method and the Line of Balance Method. The data used in this research are the dependency relationship between activities, time schedule, cost analysis plan (RAB), and SNI unit price analysis. The analysis process carried out in this study is to calculate the time needed to complete two housing units using two methods, namely the Precedence Diagram Method and the Line of Balance method. The results of this study indicate the time needed to build two housing units using the Precedence Diagram Method 7 days faster than using the Line of Balance Method.